2018
DOI: 10.1021/acs.jpcb.7b10893
|View full text |Cite
|
Sign up to set email alerts
|

Structural Origin of Shear Viscosity of Liquid Water

Abstract: The relation between the microscopic structure and shear viscosity of liquid water was analyzed by calculating the cross-correlation between the shear stress and the two-body density using the molecular dynamics simulation. The slow viscoelastic relaxation that dominates the steady-state shear viscosity was ascribed to the destruction of the hydrogen-bonding network structure along the compression axis of the shear distortion, which resembles the structural change under isotropic hydrostatic compression. It me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…The calculated numerical integral gives the shear viscosity as 0.768 ± 0.008 cP at 298.15 K from the integral eq with an upper time limit of 6 ps. There have been several previous calculations of the shear viscosity of water using a variety of force fields. Several studies have considered the TIP4P/2005 model used here and obtained values of η s = 0.78, 0.807, 0.82, 0.83, 0.855, and 0.89 cP . The measured shear viscosity is 0.8903 cP .…”
Section: Resultsmentioning
confidence: 91%
See 1 more Smart Citation
“…The calculated numerical integral gives the shear viscosity as 0.768 ± 0.008 cP at 298.15 K from the integral eq with an upper time limit of 6 ps. There have been several previous calculations of the shear viscosity of water using a variety of force fields. Several studies have considered the TIP4P/2005 model used here and obtained values of η s = 0.78, 0.807, 0.82, 0.83, 0.855, and 0.89 cP . The measured shear viscosity is 0.8903 cP .…”
Section: Resultsmentioning
confidence: 91%
“…That is, it is not clear how to define a reaction coordinate that takes the system over the barrier. However, several analyses support the notion that for water it is closely related to the exchange of H-bonds , and the similarity of the activation energy to that for diffusion ( vide infra ), reorientation, , and H-bond exchange itself , supports this conclusion.…”
Section: Resultsmentioning
confidence: 94%
“…The macroscopic viscosity is one example for properties that reflect such non-local dynamics. [30][31][32][33] For non-associated liquids, Eyring proposed as early as in 1936 that the thermally activated translation of a single molecule provides a good description for viscous flow, which in turn predicts viscosity to scale with the square root of the molecular mass. 34 For hydrogen-bonded liquids, however, correlated molecular motions, i.e.…”
mentioning
confidence: 99%
“…the restructuring of the hydrogen-bonding network alters viscosity. [30][31][32][33] This structural rearrangement also involves rotational motions of water molecules, 33,35,36 for which the rate scales with the inverse square root of the moments of inertia. 6 Viscometric experiments using isotopic 16 O/ 18 O substitution, which alters the moments of inertia of a water molecule by B0.6% but increases its molecular mass by B13%, have however shown that the B5% increase in viscosity is consistent with a translational mass factor, ffiffiffiffiffiffiffiffiffiffiffiffiffiffiffiffiffiffiffiffiffiffiffiffiffiffiffiffiffiffiffiffiffiffiffiffiffiffiffiffiffiffiffiffiffi…”
mentioning
confidence: 99%
“…After confirming that the maximum of the volume viscosity was reproduced, the analysis of the mechanism was performed through the cross-correlation between the adiabatic pressure fluctuation and the two-body density, as we performed for the analysis of shear viscosity of various liquids including neat liquid methanol. [15][16][17]…”
Section: Introductionmentioning
confidence: 99%